Pembatalan Wasiat Dan Dampak Hak Waris Terhadap Hilangnya Legitieme Portie Berdasarkan Putusan Pengadilan Nomor 43/PDT.G/2020/PN Medan - Abdullah, Risyad; Fendri, Azmi; Fauzi, Wetria (LPPM Universitas Ekasakti Padang, 2024)
Every transfer of property during a marriage as long as the marriage is not agreed upon, every act of transfer and collateral must obtain the approval of each married partner so that if there is a transfer of joint property during the marriage, the action will be null and void. The formulation of the problem in this research is: What is the basis of the judge's considerations in the case of Court Decision Number 43/Pdt.G/2020/PN Medan relating to the cancellation of wills and the impact of inheritance rights on the loss of Legitiieme Portie? And what are the legal consequences of canceling a will for the parties in the case of Court Decision Number 43/Pdt.G/2020/PN Medan relating to the cancellation of a will and the impact of inheritance rights on the loss of Legitieme Portie? The method in this research is nomative juridical. A notary making an authentic deed is legal principles contained in the Civil Code in connection with making a will deed where a notary cannot make a will deed that bequeaths or bequeaths mixed assets in a marriage that owns the property. is joint ownership, because the action taken will harm the married couple so that it can be betrayed as an unlawful act as in the case in Decision Number 43/PDT.G/2020/PN. Medan. The resolution of the case stems from the return of the wife's rights to some of the assets in the mixture of her marital assets, namely half, while the other half is the inheritance deed of the deceased which should still be inherited by the deceased's heirs